Double sequential cardioversion for refractory ventricular tachycardia: A case report. (23rd January 2018) - Sheikh, Hasan; Xie, Edward; Austin, Emily
ABSTRACT: Sustained monomorphic ventricular tachycardia (VT) can result in hypoperfusion or devolve into more dangerous rhythms such as ventricular fibrillation. In an unstable patient with VT and a pulse, synchronized cardioversion is the first-line treatment. When the VT is refractory to standard cardioversion, the next step is to add an antiarrhythmic, such as amiodarone, that carries with it the risk of lowering blood pressure in the already hypotensive patient. Here we describe a case of double sequential synchronized cardioversion of a patient with unstable VT refractory to standard direct current cardioversion, resulting in a rapid conversion to sinus rhythm and return to hemodynamic stability. The benefit of this technique is that it may obviate the need for rapid infusion of medications, such as amiodarone, in the acute setting that may worsen hypotension in the already unstable patient. RÉSUMÉ: La tachycardie ventriculaire (TV) monomorphe soutenue peut entraîner de l'hypoperfusion ou évoluer vers des troubles du rythme encore plus dangereux tels que la fibrillation ventriculaire. Le traitement de première intention de la TV chez les patients ayant un pouls perceptible est la cardioversion synchronisée. Si la TV se montre réfractaire à la cardioversion normale, l'étape suivante consiste en l'adjonction d'un antiarythmique tel que l'amiodarone, mais le traitement risque d'abaisser la pression artérielle chez des patients déjà en état d'hypotension. Sera exposé ici un cas tachycardie ventriculaire réfractaire à la cardioversion normale à courant continu, traitée par une cardioversion synchronisée séquentielle double, qui a permis un passage rapide au rythme sinusal et un retour à la stabilité hémodynamique. La technique offre peut-être l'avantage de rendre inutile la nécessité d'une perfusion rapide de médicaments comme l'amiodarone dans les cas urgents, traitement susceptible d'aggraver l'hypotension chez des patients déjà instables.